Volume 10: Micro- And Nano-Systems Engineering and Packaging 2014
DOI: 10.1115/imece2014-40214
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Scale Regular-Fractal Topography Characterization and Modeling

Abstract: Regular-fractal topography on RF-switch MEMS surface is reported over different scale ranges. Surface topography is crucial in understanding underling physics associated with the surface contacts, switch working performance, and reliability. The complexity of these structures requires new techniques to characterize topography and then replicate the multi-scale regular-fractal structure for analysis. Topography on RF-switch contacting surfaces are scanned by atomic force microscopy (AFM) at different length sca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…The newly emerged smaller contact spots can be observed close to the edge of existed larger contact zones. In Liu's work [44], it was shown that a fractal surface structure is statistically homogeneous or 'standing out' asperities spread more likely uniform and spatially separate. The asperity merge on pure fractal surfaces may tend to bring about fewer asperities together than on regular-fractal surfaces on that the merge bring about more closely clustered asperities on top of bumps, therefore forms many isolated smaller contacting islands all over.…”
Section: Contact Mechanics Regular-fractal Patternmentioning
confidence: 99%
“…The newly emerged smaller contact spots can be observed close to the edge of existed larger contact zones. In Liu's work [44], it was shown that a fractal surface structure is statistically homogeneous or 'standing out' asperities spread more likely uniform and spatially separate. The asperity merge on pure fractal surfaces may tend to bring about fewer asperities together than on regular-fractal surfaces on that the merge bring about more closely clustered asperities on top of bumps, therefore forms many isolated smaller contacting islands all over.…”
Section: Contact Mechanics Regular-fractal Patternmentioning
confidence: 99%